OSTEOARTHROSIS TOGETHER WITH OSTEOPOROSIS - AN URGENT PROBLEM OF RHEUMATOLOGY - Bobaev, N.M (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The risk factors for osteoporosis in patients with osteoarthrosis were studied. An analysis of the available literature has shown that in most patients with osteoarthrosis more than one risk factor plays a role in the development of osteoporosis, which necessitates a screening examination of patients for early detection and prevention of osteoporosis in individuals with osteoarthritis.